Management of Ecopesantren Curriculum Development in Forming The Ecopreneurship of Santri - Rihlah Nur Aulia; Hafid Abbas; Nurhattati (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
This study aims to find a model for Ecopesantren curriculum development in shaping students' ecopreneurship. This research uses the management theory of curriculum development. The methodology used in this research is a qualitative case study methodology. This research concludes: first, Pesantren SPMAA implements a different management curriculum from other Islamic boarding schools in Indonesia. Second, in the management or management of the Pesantren SPMAA curriculum refers to the National curriculum, and the third, ecopesantren curriculum, curriculum management includes; curriculum planning: curriculum mapping, syllabus, inquiry program, inquiry unit, unit learning planning. Simultaneously, organizing the curriculum consists of curriculum structure, division of teacher duties, development of transdisciplinary programs, development of transdisciplinary programs, determining units of inquiry for each grade level. Moreover, the implementation of the curriculum consists of learning experiences, assessments, and learning outcomes reports. Meanwhile, curriculum evaluation consists of unit reviews and two subject reviews—review units and review subjects.